iOS 12 programming fundamentals with Swift Swift, Xcode, and Cocoa basics - Neuburg, Matt (O'Reilly Media, 2018)
Move into iOS development by getting a firm grasp of its fundamentals, including the Xcode 10 ODE, Cocoa Touch, and the latest version of Apple's acclaimed programming language, Swift 4.2. With this thoroughly updated guide, you'll learn the Swift language, understand Apple's Xcode development tools, and discover the Cocoa framework